Response of bedwetting to the enuresis alarm. Influence of psychiatric disturbance and maximum functional bladder capacity. Issue 5 (May 1982) - Berg, I; Forsythe, I; McGuire, R
Abstract : Fifty-four children with nocturnal enuresis were managed with the pad and bell system. Their maximum functional bladder capacity was estimated before they began treatment, and a Rutter A questionnaire was completed by the mothers. If an average of less than one wet night a week is taken as a criterion of success, then 63% of them responded in the last month of treatment; neither the Rutter score nor the maximum functional bladder capacity predicted outcome. However 26% failed to persist with treatment to the end of the project and were considered to have dropped out. If they are excluded, the initial response rate is 73%. In these cases a Rutter total score of at least 18 was found to be associated with failure to respond, but the maximum bladder capacity was not related to outcome.